Peran Astra Daihatsu Motor Dalam Program Konservasi Penyu Di Indonesia - Muhammad Faiz Parikesit (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Sea Turtle conservation has become a significant focus in preserving Indonesia's rich marine ecosystem biodiversity. Astra Daihatsu Motor is one of the active companies contributing to conservation efforts. Through their commitment to corporate social responsibility and environmental concern, Astra Daihatsu Motor has been actively involved in various turtle protection programs in coastal areas across Indonesia. In its involvement, Astra Daihatsu Motor not only provides financial support but also contributes to fundraising efforts, raising public awareness, and enhancing the necessary infrastructure for turtle habitat preservation. These measures include establishing research centers, awareness campaigns, training for local communities, and setting up conservation facilities. Thus, the role of Astra Daihatsu Motor in sea turtle conservation programs in Indonesia not only reflects the company's commitment to environmental sustainability but also inspires other businesses and communities to participate in the preservation of species vulnerable to extinction.